Blockchain technology applications in the supply chain: a critical analysis - Ahmed, Wafaa Ahmed Hamed (2022)
Blockchain is a combination of technologies comprising a digital chain of records that are time-stamped, uniquely identified, and stored in chronological order. It has been recognised as a potentially disruptive technology due to its core characteristics, including decentralisation, immutability, security, transparency, and traceability. Blockchain has captured the interest of many organisations that are increasingly experimenting with the technology in various applications ranging from financial services to healthcare and logistics and supply chain management. Supply chain academics and professionals have acknowledged the potential of blockchain to transform supply chains and operations management. However, the academic literature on blockchain applications in the supply chain lags behind its applications in practice and is mostly conceptual with limited empirical research. Many blockchain implementations in practice do not go beyond the pilot stage. Industry professionals lack evidence-based guidance on blockchain capabilities and potential applications in the supply chain. Thus, it is crucial to conduct empirical research to provide an in-depth analysis of blockchain’s capabilities and its potential implications for supply chains to provide guidance on the main considerations related to its adoption, application and scalability. This research investigates empirically the main motivations behind blockchain adoption and the main pre-requisites, inhibitors and factors influencing blockchain adoption and scalability within different supply network configurations. It also examines the influence of sectoral characteristics on blockchain adoption and applications in the different industries. The study uses mixed research methods, including multiple case studies of leading organisations at different stages of blockchain adoption and across different industries, an analysis of secondary data sources for reported blockchain use cases, and an executive workshop that debated blockchain-enabled supply chain traceability. The research findings provide comprehensive guidelines for blockchain adoption in the supply chain from the pre-adoption stage to the scaling of blockchain across supply networks. The research identifies the main industry motivations, main application areas and specific sectoral characteristics influencing blockchain adoption and application in the supply chain. The research also studies the decision-making process for blockchain adoption and application in the supply chain. The study also provides specific guidance for one of the most critical application areas for blockchain - supply chain traceability. This research has significant theoretical and practical contributions for this emerging and prominent field. It provides new empirical evidence to the main motivations behind blockchain adoption in the supply chain, highlighting the importance of new considerations not discussed in the literature, including customer service, risk management and quality assurance. The research also develops three important frameworks: First, it proposes the first cross-sectoral framework that captures the main motivations, application areas and industry characteristics that influence blockchain adoption and application in the supply chain. This framework can lay the foundation for future research that can further investigate the different associations identified in the framework between the motivations, application areas and industry characteristics. Second, the research proposes the first decision model that provides guidance to the selection of blockchain technology and its application area in the supply chain. Third, the research proposes a framework for theory that identifies different combinations of theoretical perspectives to further study and contribute to theory development in the blockchain-SCM research. The research findings and developed frameworks provide detailed guidance to practitioners interested in investigating and adopting blockchain in their supply chain.